The Influence of Climate Conditions and On-Skin Positioning on InGaZnO Thin-Film Transistor Performance - Catania, Federica; Oliveira, Hugo De Souza; Costa Angeli, Martina A.; Ciocca, Manuela; Pané, Salvador; Münzenrieder, Niko; Cantarella, Giuseppe (Frontiers in Electronics, 2022)
Thin-film transistors (TFTs) based on amorphous indium-gallium-zinc-oxide (a-IGZO) have proved promising features for flexible and lightweight electronics. To achieve a technological maturity for commercial and industrial applications, their stability under extreme environmental conditions is highly required. The combined effects of temperature (T) from -30.0°C to 50.0°C and relative humidity (RH) stress from 0% to 95% on a-IGZO TFT is presented. The TFTs performances and the parameters variation were analysed in two different experiments. First, the TFT response was extracted while undergoing the most extreme climate conditions on Earth, ranging from African Desert (50.0°C, 22%) to Antarctic (-30.0°C, 0%). Afterwards, the device functionality was demonstrated in three parts of the human body (forehand, arm and foot) at low (35%), medium (60%) and high (95%) relative humidity for on-skin and wearable applications. The sensitivity to T/RH variations suggests the suitability of these TFTs as sensing element for epidermal electronics and artificial-skin.